Deteksi Ujaran Kebencian pada Komentar Instagram dalam Bahasa Indonesia Menggunakan Metode Recurrent Neural Network - Hengky; Yulius Denny Prabowo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Hate speech is any form of communication that are provoking and bringing down a group or individual. The objective of this study is to create a model that can detect hate speech on Instagram comments in Indonesian language. The method used in this study is Recurrent Neural Network. This study produces a model that can detect hate speech with an accuracy